The results of the state variety examination of the soft winter wheat seeds quality (Triticum aestivum L.), which are included in to the State Register of plant varieties of Ukraine - О. О. Шовгун; В. В. Шелепов; В. М. Лисікова; С. О. Ляшенко; С. Л. Чухлєб; О. О. Бадяка (Plant Varieties Studying and Protection)
According to the seed quality indices the soft winter wheat seeds quality which were included in to the State Register of ріалі varieties of Ukraine in 2008 was defined (consistence of the albumen, flour s-rength. bread size). In the steppe area the consistence of albumen in seed was not changed. In the forest-steppe area seed quality markers improved and drew near the seed quality markers of the steppe area. More then 80% of wheat varieties, produced by Ukrainian breeders are considered to be strong and valuable by the seed quality verse 19,4 % of foreign varieties. That means that the varieties of the Ukrainian breeding are competitive.